Cesium lead iodide electrospun fibrous membranes for white light-emitting diodes. (17th September 2022) - Wang, Qi; Li, Ke; Yang, Haohan; Lin, Donghai; Shih, Wan Y; Shih, Wei-Heng
Abstract: Inorganic perovskite cesium lead iodide nanocrystals (CsPbI3 NCs) are good candidates for optoelectronic devices because of their excellent properties of remarkable luminous performance (high luminous efficiency, narrow luminous spectral line), and high photoelectric conversion efficiency by using simple preparation method. But their inherent poor stability greatly limits its practical applications. In this paper, electrospinning is used to grow fibrous membranes with embedded cesium lead iodide perovskite nanocrystals (PNCs) formed in situ in a one-step process. It was found that cubic α -CsPbI3 PNCs were formed in polymer fibers, showing bright and uniform fluorescence signals. Furthermore, the water wetting angles were increased by the fibrous structure enhancing the hydrophobicity and the stability of the fibrous membranes in water. The electrospun fibrous membrane containing CsPbI3 was combined with another membrane containing CsPbBr3 under a blue light-emitting diode (LED) to create a white LED (WLED) in air successfully with CIE coordinates (0.3020, 0.3029), and a correlated color temperature of 7527 °K, indicating high purity of WLED. Our approach provides a new way to create highly stable, photoluminescent water-resistant perovskite nanocrystalline films.